see image

What is the equation of this circle in general form? answer choices below image

x2+y2−6x+4=0

x2+y2−6x−16=0

x2+y2+6x−16=0

x² + y² + 6x + 4 = 0

CrazyDaizy
Jun 6, 2017

#1**+1 **

From looking at the graph, we can see that

the center of this circle is the point (**3**, **0**) and

the radius of this circle is **5** units.

So, the equation of this circle in standard form is:

(x - **3**)^{2} + (y - **0**)^{2} = **5**^{2} Simplified, this is....

(x - 3)^{2} + y^{2} = 25

To get this equation in general form, first multiply out the (x - 3)^{2 }.

(x - 3)(x - 3) + y^{2} = 25

x^{2} - 3x - 3x + 9 + y^{2} = 25 Subtract 25 from both sides of the equation.

x^{2} - 3x - 3x + 9 + y^{2} - 25 = 0 Combine like terms and rearrange.

x^{2} + y^{2} - 6x - 16 = 0

hectictar
Jun 6, 2017

#1**+1 **

Best Answer

From looking at the graph, we can see that

the center of this circle is the point (**3**, **0**) and

the radius of this circle is **5** units.

So, the equation of this circle in standard form is:

(x - **3**)^{2} + (y - **0**)^{2} = **5**^{2} Simplified, this is....

(x - 3)^{2} + y^{2} = 25

To get this equation in general form, first multiply out the (x - 3)^{2 }.

(x - 3)(x - 3) + y^{2} = 25

x^{2} - 3x - 3x + 9 + y^{2} = 25 Subtract 25 from both sides of the equation.

x^{2} - 3x - 3x + 9 + y^{2} - 25 = 0 Combine like terms and rearrange.

x^{2} + y^{2} - 6x - 16 = 0

hectictar
Jun 6, 2017